The kite project to improve junior high school students’ numeracy - Nabila Putri Isamer; Ratu Ilma Indra Putri; Zulkardi Zulkardi (Jurnal Elemen, 2023)
This research occurred to improve students' numeracy skills. To help students acquire these skills, develop learning projects through a STEAM approach using kite-making and collaborative learning projects. Design collaborative learning projects using a STEAM approach to assist students in acquiring these skills. This study's primary purpose is to create kites to aid junior high school students in addressing problems concerning PLSV and the kite area. This study applies a design research type of validation study. The data collection technique used is using images, products, and review documents for data collecting. The research participants were 30 seventh-grade (Phase D) junior high school students in Palembang. This study developed a learning trajectory that includes three exercises and post-test questions. Students can investigate and address issues associated with kite construction using PLSV materials. In the second activity, students can create kites and estimate their area based on their kite-making skills. After the kite is built, students fly a kite and study it. Students can improve their numeracy abilities through project-based learning employing STEAM in the context of kite creation, as demonstrated by the findings of this study. This knowledge aids them in overcoming obstacles associated with PLSV content and expands kite-making.